2012
DOI: 10.4049/jimmunol.1202084
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Allograft Survival by Inhibitory FcγRIIb Signaling

Abstract: Fc gamma receptors (FcγR) provide important immunoregulation. Targeting inhibitory FcγRIIb may therefore prolong allograft survival, but its role in transplantation has not been addressed. FcγRIIb signaling was examined in murine models of acute or chronic cardiac allograft rejection by transplanting recipients that either lacked FcγRIIb expression (FcγRIIb−/− ) or over-expressed FcγRIIb on B cells (BTG). Acute heart allograft rejection occurred at the same tempo in FcγRIIb−/− C57Bl/6 (B6) recipients as WT rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 70 publications
1
31
1
Order By: Relevance
“…In this model, a chronic vasculopathy is observed, analogous to that in human hearts with chronic rejection, which is driven by autoantibody production. FcγRIIB-deficient mice demonstrated elevated autoantibody production and more severe arteriopathy [66•]. These data are consistent with the known role for FcγRIIB in regulating B cells, but this study did not dissect the relative effect of FcγRIIB on B cells versus myeloid cells.…”
Section: Fcγrs and Abmrsupporting
confidence: 79%
“…In this model, a chronic vasculopathy is observed, analogous to that in human hearts with chronic rejection, which is driven by autoantibody production. FcγRIIB-deficient mice demonstrated elevated autoantibody production and more severe arteriopathy [66•]. These data are consistent with the known role for FcγRIIB in regulating B cells, but this study did not dissect the relative effect of FcγRIIB on B cells versus myeloid cells.…”
Section: Fcγrs and Abmrsupporting
confidence: 79%
“…19 However, several studies also implicate a pathogenic role for IgG in atherosclerosis, albeit indirectly, [20][21][22] and vascular pathologies, such as chronic cardiac rejection and large vessel vasculitis, are thought to be driven by pathogenic autoantibodies. 23,24 Emerging paradigms reveal many non-antibody-dependent functions of B cells that could play important roles in atherosclerosis. [25][26][27] We and others have shown follicular B2 cell interactions with CD4 + T cells, antagonized by marginal zone B2 cells, promote pathogenic T cell responses in the atherosclerotic setting.…”
Section: Meet the First Author See P 198mentioning
confidence: 99%
“…The inhibitory FcRIIB is the most broadly expressed FcR, and is present on virtually all leukocytes with the exception of NK cells and T cells and are involved in endocytosis or phagocytosis of immune complexes (33). A recent study on FcRIIb signaling in cardiac allografts in mice showed that it regulates chronic but not acute rejection (34). Authors postulated that helper CD4 T cell response in acute rejection overcomes FcRIIb-mediated inhibition of the effector B cell population.…”
Section: Evolving Pathogenesis Of Antibody Mediated Renal Allografmentioning
confidence: 99%
“…Authors postulated that helper CD4 T cell response in acute rejection overcomes FcRIIb-mediated inhibition of the effector B cell population. Similar studies in renal allografts are lacking (34). In another study in cardiac allografts in mice, monoclonal alloantibodies to immunoglobulin to MHC I antigens can augment graft injury by stimulating EC to produce MCP-1 and by activating mononuclear cells through their Fc receptors.…”
Section: Evolving Pathogenesis Of Antibody Mediated Renal Allografmentioning
confidence: 99%